Assessment of sensory preference and frequency of carbohydrate bar consumption by physically active people - Kiciak, Agata; Czaderna, Ewa; Staśkiewicz, Wiktoria; Piątek, Małgorzata; Bielaszka, Agnieszka; Kardas, Marek (Journal of Education, Health and Sport, 2022)
Introduction: Active lifestyles are causing an increase in interest directed toward foods, many athletes use specially formulated food products that concentrate large amounts of nutrients in a small volume, while also being easily digestible and quickly absorbed. The main objective of the study was to compare selected commercially available products prepared for physically active people with those prepared based on proprietary recipes and natural, commonly available ingredients. Material and method: The material used in the comparative study was energy bars from three sources: popular market bars from the leading manufacturers in the Polish market and available in most grocery stores, specialized bars, and bars made according to the author's recipe in imitation of the above snacks using natural ingredients. The evaluation of the use of supplements was based on the author's survey questionnaire on consumer preferences and frequency of consumption of carbohydrate products, using energy bars as an example. Results: Bars prepared according to the author's recipe received scores of 2 and 3 for taste and texture and scores of 1 and 2 for the input of basic raw materials. Evaluation of the use of supplements was carried out in a group of 147 people, the study group was dominated by people who train in cycling and running. About 65% of the respondents declared that they use energy bars. Among those who use energy bars, the largest number of respondents declared that they use specialty bars (20%), 15% of respondents use market bars and 8% make the bars themselves. Conclusions: The results of the sensory evaluation of bars prepared according to the author's recipe indicate the need to modify their composition, especially in terms of improving the texture. Carbohydrate supplements are used by respondents, especially if it is justified in the case of practicing endurance and endurance sports characterized by high intensity of training, i.e. cycling and running.